Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Protonindo Citra Jakarta Barat - Hermana, Cecep; Pratama, M. Aditya Anugrah (SEIKO : Journal of Management & Business, 2023)
Human Resource Development is always mentioned in the company's vision and mission, but sometimes companies rarely analyze factors that can affect the performance of their employees. The factors that affect the employee's performance include work stress and work environment. So this study aims to determine the effect of work stress and work environment on employee performance at PT. Protonindo Citra, West Jakarta. The method used is descriptive verification with a quantitative approach. Data analysis using path analysis and hypothesis testing using t test and f test. The results showed that the variables of work stress and work environment have a strong and positive relationship. Partially job stress has a significant effect on employee performance, then the work environment has a significant effect on employee performance. Furthermore, simultaneously work stress and environmental variables have a significant influence on employee performance. Keywords: Job Stress, Work Environment, Performance, and Human Resources